Drivers in the conservation of urban green space depletion: A case study of Wa Municipality, Ghana - Sabastian Batasuma; Wei Cao; Nathan Awelama Atigah; Emefa Acorlor Garnet; Joshua Kojo Bonzo; Justice Gyimah (City and Environment Interactions)
In rapidly developing regions, especially in emerging economies like Ghana, the decline of greenery is an urgent concern. This ongoing trend leads to the significant loss of land and green areas, which worsens environmental challenges and imposes substantial costs on Local as well as state governments. This study focuses on the Wa Municipality, examining the interplay between urbanization, regulatory policies, and human behavior in influencing green space loss.The innovation of this research lies in its integrated approach, combining qualitative insights with regression analysis to uncover complex dynamics affecting urban green spaces. Using statistical analysis and qualitative insights combined, the study revealed that while regulatory policies play a positive role in the preservation of green spaces (with a regression coefficient of Rp = 1.07, p < 0.01), both urbanization (Ur = -0.14, p < 0.05) and human behavior (Hb = -0.34, p < 0.05) significantly contribute to their decline.These findings highlight the critical need for robust legal frameworks and active community engagement to mitigate the negative effects of environmental degradation. In addition, the study emphasizes the need of reducing sprawl in cities and offers an adaptable framework that can be modified to other urban situations both within and outside of the region, offering policymakers and city planners relevant data. By implementing the strategies identified in this research, stakeholders can promote sustainable urban development and protect vital green spaces, thereby ensuring a healthier environment for current and future generations.